Numerical investigation on thermal performance of battery module with LCP‐AFC cooling system applied in electric vehicle. Issue 12 (10th August 2022) - Guo, Huizhen; Li, Juan; Zhu, Zhangyu; Lv, Peihong
Abstract: To improve the thermal performance of electric vehicle batteries, a novel cooling system of liquid cold plates coupled with air flow channels (LCP‐AFC) for battery thermal management was proposed. Three‐dimensional models were established for simulation. The effects of five factors on the heat dissipation of the electric vehicle battery module were studied, which included the battery discharge rate, inlet temperature of cooling liquid, nanofluids, airflow velocity, liquid, and air flow directions. The results showed that the maximum temperature T max and temperature difference Δ T of the battery module under 1 C discharge rate could be reduced by 1.1°C and 0.92°C compared to the single liquid cooling. Comparing the LCP‐AFC with single air cooling, the T max and Δ T of the battery module under 4 C discharge rate could be reduced by 18.74°C and 2.71°C. The temperature uniformity of the battery module was not satisfied with the inlet temperature of the cooling liquid, which was lower than 15°C. The heat transfer performance was improved by adding Al, Cu, or Ag nanoparticles into the deionized water. Among them, Ag–water nanofluid had the most significant cooling effect. Parallel flow indicated better thermal performance than cross flow and counter flow. The developed cooling system of LCP‐AFC offers a new method to design lithium‐ion battery thermal management system for controlling temperature distribution of a battery module. Abstract : A new cooling system of liquid cold plate coupled air flow channels was designed for thermal management of lithium‐ion battery module. The effects of five factors on the heat dissipation of the electric vehicle battery module were studied, which include battery discharge rate, inlet temperature of cooling liquid, nanofluids, air flow velocity, liquid and air flow direction. The maximum temperature and temperature difference were used to evaluate the effectiveness of thermal management.